Distinct effects of progesterone and cholesterol on lipid membranes: insights from biophysical experiments and molecular dynamics simulations - Lągowska, Anna; Krok, Emilia; Domanska, Maria; Setny, Piotr; Piatkowski, Lukasz; Orlikowska-Rzeznik, Hanna (Frontiers in Molecular Biosciences, 2025)
Steroid hormones, including progesterone, are known to exert genomic, non-genomic and non-specific effects. However, their influence on membrane biophysics remains unclear. In this study, we investigate the distinct membrane-modulating behaviour of progesterone compared to cholesterol, employing a multidisciplinary approach that combines fluorescence microscopy, steady-state spectroscopy, and atomistic molecular dynamics simulations. Our results demonstrate that, whereas cholesterol promotes lipid packing and stabilises phase-separated domains, progesterone disrupts phase separation, reduces line tension and increases lipid lateral diffusion, without significantly altering local membrane fluidity. Molecular simulations reveal that progesterone is more variably oriented and distributed within the bilayer than cholesterol. This results in membrane thinning and differential ordering of lipid tails. These structural effects may lead to increased membrane permeability and dynamic reorganization, which could facilitate rapid non-genomic signalling. Notably, the effects of progesterone are more pronounced in multicomponent, phase-separated membranes than in homogeneous lipid systems, suggesting context-specific roles. Our findings present progesterone as a dynamic modulator of membrane organisation, with implications for hormone signalling, drug delivery and therapeutic action in pharmacological settings.